Fatigue Characteristics of Prestressed Concrete Beam under Freezing and Thawing Cycles. (4th September 2020) - Zheng, Yuanxun; Yang, Lei; Guo, Pan; Yang, Peibing
Abstract : In order to reveal the influence of freezing and thawing on fatigue properties of the prestressed concrete beam, a kind of novel freeze-thaw test method for large concrete structure components was proposed, and the freeze-thaw experiments and fatigue failure test of prestressed concrete hollow beams were performed in this paper. Firstly, the compressive strength and dynamic elastic modulus of standard specimens subjected to different numbers of freeze-thaw cycles (0, 50, 75, and 100) were determined. Then, the static and dynamic experiments were performed for prestressed concrete beams under different freeze-thaw cycles. Depending on the static failure test results, the fatigue load for the prestressed concrete beam model was carried out, the fatigue tests for prestressed concrete beam under freezing and thawing cycles were done, and the influence of fatigue loading times on dynamic and static characteristics of prestressed concrete beam was also studied. Finally, the relation between fatigue characteristics and numbers of freeze-thaw cycles was established, and the fatigue life prediction formulas of prestressed concrete beams under freeze-thaw cycles were developed. The research shows that the freezing and thawing cycles had obvious influence on fatigue life, and the freezing and thawing cycles should be taken into account for life prediction and quality evaluation of prestressed concrete beams.